Nurse training to enhance adherence counselling for HIV-tuberculosis coinfection in South Africa: Integrative review - Victoire Ticha; Million Bimerew; Rene D. Phetlhu (Curationis)
Background: South Africa has seen strides in reducing HIV and tuberculosis (TB); however, adherence counselling for people living with HIV (PLHIV) coinfected with TB remains a challenge, particularly in specific sub-districts like Cape Town. Understanding the attributes of existing training programmes is crucial.